THE INFLUENCE OF FIRM FINANCIAL PERFORMANCE ON DIVIDEND POLICY AND ITS EFFECT TO THE FIRM VALUE (Study at Manufacturer Companies Listed in Indonesia Stock Exchange for the Period of 2010-2012) - Novita, Evaria; Rahardjo, Kusdi; Suyadi, Imam (Profit: Jurnal Adminsitrasi Bisnis, 2016)
The objectives of this research are to analyze the influence of firm financial performance on dividend policy and its effect to the firm value of manufacturer companies listed in Indonesian Stock Exchange (IDX) for the periof of 2010-2012 and give recommendations as the completion upon this research. By applying  Generalized  Structured  Component  Analysis  (GSCA)  of  19  sample  used,  the  analysis attempts to examining the influence among variables. This research uses current ratio (CR), debt to equity ratio (DER), return on common equity (ROE), earning per share (EPS), and price to book value (PBV) as the variables of firm financial performance, dividend payout ratio (DPR) as the variable of dividend policy, and closing stock price as the variable of firm value. Result of the research reveal that CR has no significant influence on DPR, however CR has a positive and signifant influence on stock price. DER has no significant influence to the DPR and also to the stock price. ROE, EPS, and PBV has a positive and significant influence to the DPR and also to the stock price. Furthermore, DPR has a positive and significant influence on stock price. The present research confirms that firm financial performance, dividend policy, and firm value is the essential and important aspect for the investors in determining the profitable stocks. Therefore, it is very useful for investors to considerate these variable of research in order to make the right investment decisions and do stock trading confidently.